2016
DOI: 10.1002/cphc.201600653
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Drives Calcium Carbonate Ion Association

Abstract: The understanding of the molecular mechanisms underlying the early stages of crystallisation is still incomplete. In the case of calcium carbonate, experimental and computational evidence suggests that phase separation relies on so-called pre-nucleation clusters (PNCs). A thorough thermodynamic analysis of the enthalpic and entropic contributions to the overall free energy of PNC formation derived from three independent methods demonstrates that solute clustering is driven by entropy. This can be quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 53 publications
(107 reference statements)
9
124
1
2
Order By: Relevance
“…2 indicate that crystallinity emerges only during the decrease in height as amorphous 3D nanoscopic entities transform into crystalline 2D layers12. In the present case, we hypothesize that the release of water from hydrated disordered precursors back into the surrounding solution is entropically favourable, and thus drives the assembly of remaining solute molecules into an ordered structure on the underlying parent crystal substrate44.…”
Section: Resultsmentioning
confidence: 60%
“…2 indicate that crystallinity emerges only during the decrease in height as amorphous 3D nanoscopic entities transform into crystalline 2D layers12. In the present case, we hypothesize that the release of water from hydrated disordered precursors back into the surrounding solution is entropically favourable, and thus drives the assembly of remaining solute molecules into an ordered structure on the underlying parent crystal substrate44.…”
Section: Resultsmentioning
confidence: 60%
“…[3] been reported to precede the ACCformation, as summarized in Figure 2. [42,43] Based on these observations,i tw as suggested that ACCf orms through aggregation of PNCs following anonclassical route. [36] In addition, clusters with aw ell-defined diameter of around 2nmh ave been observed by analytical ultracentrifugation (AUC), [36] cryogenic transmission electron microscopy (cryo-TEM), [39] and small-angle X-ray scattering (SAXS).…”
Section: Formation Of Accmentioning
confidence: 99%
“…First, the destabilizers of ion-association, such as betaine and ectoine, are possibly excluded from the hydration shells of ion-clusters. Since ion association of CaCO 3 PNCs is driven by the release of hydration waters [29], stabilized hydration shells would have adverse effects. Indeed, molecular dynamics simulations reveal that ectoine is preferentially excluded from macromolecular surfaces, leading to a dense hydration layer [72].…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose, sorbitol, ectoine, mannitol, and betaine induce increases in the pre-nucleation slope in comparison to the relative reference experiments at both pH values. At pH 9.0, this corresponds to percentage increases of about 87,44,29,26, and 20%, respectively. At higher pH (9.75), these effects are more pronounced, leading to corresponding increases of about 41,56,66,109, and 39% in the pre-nucleation slope.…”
Section: On Kosmotropes and Chaotropesmentioning
confidence: 99%